Generation and Management of Faecal Sludge Quantities and Potential for Resource Recovery in Phnom Penh, Cambodia - Eliyan, Chea; McConville, Jennifer R.; Zurbrügg, Christian; Koottatep, Thammarat; Sothea, Kok; Vinnerås, Björn (Frontiers in Environmental Science, 2022)
At the current rate of progress, there will probably still be 2.8 billion people world-wide without safely managed sanitation by 2030. To incentivise and increase implementation of sustainable faecal sludge management (FSM), especially in low and middle-income countries like Cambodia, human waste must be regarded as a resource. However, planning data, e.g. on the quantities, composition and fate of faecal sludge after leaving households, are inadequate and lack accuracy. The aim of this study was to provide baseline data for effective FSM planning by sanitation stakeholders in Phnom Penh. This was done by quantifying sludge volumes generated, transport logistics and resource recovery potential to incentivise sustainable management. Interviews were conducted with users and emptying and transportation contractors, together with collection of technical data about on-site sanitation systems. Geographical coordinates of household sampling locations and disposal sites were also mapped. The results revealed that Cheung Ek and Kob Srov wetlands are the main recipients of faecal sludge collected in Phnom Penh with the amount of 18,800m3 and 13,700m3 annually, respectively. The analysis showed that faecal sludge in Phnom Penh contains valuable resources such as nitrogen (6tons), phosphorus (13tons) and energy (148-165GWh) annually, but in-depth investigations of appropriate treatment options for resource recovery are required. Detailed documentation of the location of potential recoverable resources from faecal sludge would assist decision-makers in developing action plans for sustainable FSM in Phnom Penh and similar cities.